The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10827-013-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphology upon electrophysiological responses of retinal ganglion cells: simulation results

Abstract: Retinal ganglion cells (RGCs) display differences in their morphology and intrinsic electrophysiology. The goal of this study is to characterize the ionic currents that explain the behavior of ON and OFF RGCs and to explore if all morphological types of RGCs exhibit the phenomena described in electrophysiological data. We extend our previous single compartment cell models of ON and OFF RGCs to more biophysically realistic multicompartment cell models and investigate the effect of cell morphology on intrinsic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…However, our simulation results suggest that the dendritic integration properties of tOff alpha and tOff 388 mini RGCs could not be explained by dendritic morphology alone but require dendritic ion channels in 389 agreement with earlier simulation studies (Maturana et al, 2014). One possible reason might be that 390 for most RGCs, action potentials generated in the soma can back propagate to the dendritic arbour 391 (Velte and Masland, 1999), which needs dendritic ion channels to enable the efficient backpropagation 392 (van Rossum et al, 2003;Velte and Masland, 1999).…”
supporting
confidence: 81%
“…However, our simulation results suggest that the dendritic integration properties of tOff alpha and tOff 388 mini RGCs could not be explained by dendritic morphology alone but require dendritic ion channels in 389 agreement with earlier simulation studies (Maturana et al, 2014). One possible reason might be that 390 for most RGCs, action potentials generated in the soma can back propagate to the dendritic arbour 391 (Velte and Masland, 1999), which needs dendritic ion channels to enable the efficient backpropagation 392 (van Rossum et al, 2003;Velte and Masland, 1999).…”
supporting
confidence: 81%
“…Nonetheless, this multi-compartments model here does not represent all RGCs on account of different types and morphologies of RGCs in retina. Previous studies have shown the effect of RGC morphology on its electrophysiological responses [30]. It is worth further studying that how RGC morphology influences optimization of noise parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Each compartment was modeled as a 10-μm-long cylinder except longer dendritic branch which was 15-μm-long [29]. A schematic diagram of the cylinder model of RGC and the diameter and length of each segment [29, 30] are illustrated in Fig. 1.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have led to a quantitative understanding of many dynamical phenomena in the RGCs, including spike frequency adaptation [2], rebound activities [3,4], burst firing [4], sub-threshold activities [4], action potential (AP) initiation [5], dendritic processing [6], as well as the effect of extracellular stimuli [7], temperature [8] and cell morphology [9]. However, existing ionic models of RGCs have been largely limited to identification of individual RGC types without considering the functional significance of regional membrane channel distributions/kinetics and complex morphology.…”
mentioning
confidence: 99%